KORELASI METODE MENGAJAR DOSEN DENGAN MOTIVASI BELAJAR MAHASISWA STKIP YASIKA MAJALENGKA PADA MASA PANDEMI 2020 - Zulfardi - D (STKIP ROKANIA, 2021)
This research is metivated by the use of the method in learning Indonesian and motivation as a result of using the method. Purpose of the study to verify the research hypothesis stated in the form of a statement that is, their correlation of lecturer teaching methodswith the learning motivation of Yasikamajalengka STKIP studens during the 2020 pandemic. Type of research is quantitative descriptive method. Instruments used in this study 1) questionnaire/kuensioner and 2) interviewThe results showed that there was a significant relationship between lecturer teaching methods and learning mitivation of STKIP YasikaMajalengkastudens during the 2020 pandemic.